A gathering place for patient experience research: The power of community - Jason Wolf (The Beryl Institute, 2014)
In introducing Issue 2, we explore the power of community and its implications in shaping not only the purpose and intent of Patient Experience Journal, but of the patient experience movement itself. Community defined in this moment is simple, yet significant, the key being unity around common interest and its focus on ownership and participation. The idea of community bears great weight and has provided strong guidance and purpose for the work of experience excellence. It supports the goal of elevating the conversation, helps align the voices engaged and provides the space for listening, learning and impact. Experience Framework This article is associated with the Culture & Leadership lens of The Beryl Institute Experience Framework. (http://bit.ly/ExperienceFramework) <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Culture%20%26%20Leadership%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D" target="_blank">Access other PXJ articles related to this lens. Access other resources related to this lens